post-Traumatic Growth Following EMDR Therapy Versus Collective Post-Traumatic Growth Among the People of Gaza. - Guenissaid, Naima Ait; Khadra, Guebli (Journal of Neonatal Surgery, 2026)
Post-Traumatic Growth (PTG) is a multidimensional construct that refers to the positive psychological changes that may emerge following exposure to traumatic experiences. This work examines PTG from both an individual therapeutic perspective—through Eye Movement Desensitization and Reprocessing (EMDR)—and a collective socio-cultural perspective, as illustrated by the experience of the people of Gaza. Within EMDR therapy, PTG is conceptualized as a structured, phase-based process grounded in the Adaptive Information Processing (AIP) model. Traumatic memories, initially stored in a fragmented and emotionally charged form, are reprocessed through bilateral stimulation, leading to decreased emotional reactivity, cognitive restructuring, and integration of the traumatic experience into a coherent autobiographical narrative. Neurobiologically, EMDR facilitates reduced amygdala hyperactivation, enhanced prefrontal cortical regulation, and restored hippocampal functioning, thereby supporting emotional regulation, meaning reconstruction, and the development of personal strength, resilience, and improved interpersonal relationships. In contrast, PTG in the context of Gaza emerges as a collective phenomenon shaped by chronic and repeated exposure to war, siege, and political violence. Here, growth extends beyond individual cognition and emotional regulation to encompass shared identity, collective memory, cultural narratives, and social cohesion. National identity, religious beliefs, and communal solidarity function as meaning-making frameworks that transform suffering into collective dignity, resistance, and existential purpose. Empirical research in conflict settings demonstrates that sustained trauma does not preclude growth; rather, it may foster communal resilience, social bonding, and shared moral values that mitigate the psychological impact of adversity. Physiologically and emotionally, collective PTG is supported by social regulation of affect, communal coping mechanisms, and adaptive emotional regulation strategies. Factors such as social support, collective emotion sharing, and cultural rituals contribute to improved autonomic regulation and psychological resilience, reflecting parallels with individual-level neurobiological mechanisms observed in EMDR, including reduced stress-system activation and enhanced emotional flexibility. A comparative analysis highlights both divergence and convergence between EMDR-based individual PTG and collective PTG in Gaza. EMDR operates within a structured, safe, and therapeutic context, producing measurable individual growth through targeted neurocognitive reprocessing. Collective PTG, however, evolves within an ongoing traumatic environment and is sustained through cultural, social, and historical processes rather than clinical intervention. Despite these differences, both forms of PTG share core mechanisms: meaning reconstruction, emotional regulation, identity transformation, and the conversion of trauma from a source of threat into a resource for psychological and social growth. In conclusion, PTG should be understood as a dynamic, multi-level process that integrates neurobiological, psychological, social, and cultural dimensions. Whether facilitated through individual psychotherapy or collective resilience in contexts of chronic conflict, PTG reflects the human capacity to transform profound suffering into personal strength, shared meaning, and enduring resilience..